The Role of Transformational Leadership in Enhancing Engagement and Motivation of Millennial Employees (Management Studies and Business Journal (PRODUCTIVITY), 2024)
The millennial generation who now dominates the workforce has different communication preferences, especially in the digital era, which requires adaptation of leadership styles, in particular transformational leadership. This research aims to analyze the influence of transformational leadership towards digital communication preferences and levels of engagement of millennial employees, using the approach Systematic Literature Review which is based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISM). The research results show that the internal dimensions of transformational leadership, like individualized consideration And intellectual stimulation, significantly influences millennial employee engagement through digital communication platforms. The practical implications of this research provide insights for HR managers to better understand the communication preferences of the millennial generation and adapt leadership styles to increase employee engagement and retention in a work environment that continues to develop digitally.